EDUKASI PENTINGNYA PENGGUNAAN APD DAN HYGIENE SANITASI MAKANAN PADA TENAGA KERJA PENJAMAH MAKANAN DI DAPUR PT UME SEMBADA KABUPATEN GRESIK - Kurnia Pasa Dwi Putri; Nurul Ainiyah; Rahma Fidania Dwik Nuraini; Rizky Yon Exvivonda V.S.; Rosydah Nur Aini (Universitas Muhammadiyah Gresik, 2022)
PT. Ume Sembada Gresik is an outsourcing company that provides manpower for the cleaning section to other companies that are partners of PT. Ume Sembada. According to observations made on food handlers at PT Ume Sembada Gresik, there are already workers who comply with the use of PPE when working or when entering the packing area, but there are still some workers who do not wear PPE and do not pay attention to food hygiene. This activity aims to provide information, increase knowledge, and improve habits in the use of PPE and food sanitation hygiene in the Kitchen of PT Ume Sembada Gresik. This activity uses descriptive qualitative research methods by making observations or direct observations to respondents. Sampling of activities is the food handler workforce at the Kitchen of PT Ume Sembada Gresik. The results of this activity are that there is an increase in knowledge before and after counseling and changes in the habits of workers who are disciplined in the use of PPE and pay attention to food sanitation hygiene.